Hydraulic and water quality modeling: A tool for managing land use conflicts in inland coastal zones - Hoanh, Chu Thai; Phong, N.D.; Gowing, J.W.; To Phuc Tuong; Ngoc, N.V.; Hien, N.X. (IWA Publishing, 2009)
Tidal effect and salinity intrusion are two defining characteristics of inland coastal zones, causing, respectively, complex variations in water levels and flows in river and canal networks, and serious problems for agriculture and freshwater fishery, but bringing significant benefits for brackish water aquaculture. To evaluate these conflicts and synergies in the development of agriculture, fishery and aquaculture, this paper adopts a hydraulic and salinity modeling approach that simulates the tidal propagation and salinity intrusion, and evaluates the effects of water and land use management on these hydrology- and salinity-related phenomena in coastal zones. The paper presents the empirical results from the application of a hydraulic and salinity model specifically developed for the context of the Ca Mau peninsula, Mekong Delta, Vietnam, and also demonstrates how such a modeling approach can provide valuable policy-relevant information at different phases for water resource planning, development, operation, and management in hydrologically and environmentally sensitive coastal regions.